SiGSTU18 positively regulates saline-alkali tolerance in foxtail millet through glutathione metabolism and glutamic acid-mediated alleviation of oxidative stress and ion toxicity - Yun Li; Yuxue Zhao; Fuxing Xiang; Fangying Chen; Yanrui Xu; Xiaohu Lin; Jihan Cui; Yucui Han (Plant Science, 2026)

Characterizing wind, wave, and Stokes drift interactions in the upper ocean during Typhoon Doksuri using the COAWST model - Yaoyao Han; Changsheng Zuo; Zhizu Wang; Yucui Wang; Chengchen Tao; Xu Zhang; Juncheng Zuo (Frontiers in Marine Science, 2025)
The COAWST model is used in this study to simulate wind fields, wave fields, and Stokes drift during Typhoon Doksuri, aiming to reveal the dynamics of atmosphere-ocean-wave interactions under typhoon conditions. The COAWST model provides a more accurate simulation of typhoon wind speeds compared to ERA5 reanalysis data and the WRF model, and it offers a more precise representation of significant wave heights (Hs) than ERA5 reanalysis data and the SWAN model. The root mean square error (RMSE) of wind speed shows a reduction of 90.97% and 61.09% compared to ERA5 and WRF, respectively, resulting in an RMSE of 1.71 m/s. While the Hs correlation coefficient is 0.86. Comparative analysis indicates that COAWST has higher accuracy than WRF and ERA5, particularly in capturing the asymmetrical phenomena of wind and wave field. The high-value regions of the wind and wave fields are concentrated in the first quadrant around the typhoon center. The COAWST model output, combined with empirical orthogonal function (EOF) analysis and the Ekman-Stokes number, is used to quantitatively evaluate the contributions of wind and wave effects to ocean surface flow. The peak Stokes drift velocity reaches 0.73 m/s, with a maximum transport intensity of 13 m²/s and a transport depth of 20 meters. EOF analysis indicates that the first two modes explain over 88% of the Stokes transport. The first mode represents the spatial distribution of Stokes drift during the typhoon, while the second mode captures the temporal evolution of drift velocity. This study provides insight into atmosphere-ocean interactions during extreme weather conditions by using the COAWST model to analyze Stokes drift and its influence on ocean surface dynamics.

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Comprehensive investigation of milk oligosaccharides in different mammalian species and the effect of breed and lactation period on sheep milk oligosaccharides - Haiyan Wang; Minghui Zhang; Yucui Huo; Xiuxiu Cui; Rui He; Bei Han; Zhongfu Wang; Yuxuan Song; Xin Lv; Jing Zhang; Wupeng Ge (Food Research International, 2023)

The influence of substrates addition order on colorimetric assay based on MnO2 nanocubes: A novel turn-off H2O2 assay strategy in water-soak foods - Yanfang Zhao; Yucui Zhang; Xin Liang; Da-Peng Yang; Lei Han (Food Chemistry, 2023)

Energy metabolism involved in fertility of the wheat TCMS line YS3038 - Yucui Han; Yujie Gao; Yue Zhao; Dazhong Zhang; Chao Zhao; Fang Xin; Ting Zhu; Mingyang Jian; Qin Ding; Lingjian Ma (Planta, 2019)

Association analysis of sugar yield-related traits in sorghum [Sorghum bicolor (L.)] - Peng Lv; Guisu Ji; Yucui Han; Shenglin Hou; Suying Li; Xue Ma; Ruiheng Du; Guoqing Liu (Euphytica, 2013)

Overexpression of the Gossypium barbadense Actin-Depolymerizing Factor 1 Gene Mediates Biological Changes in Transgenic Tobacco - Jina Chi; Yucui Han; Xingfen Wang; Lizhu Wu; Guiyin Zhang; Zhiying Ma (Plant Molecular Biology Reporter, 2013)

Long-term exposure to imatinib reduced cancer stem cell ability through induction of cell differentiation via activation of MAPK signaling in glioblastoma cells - Yucui Dong; Qinglian Han; Yan Zou; Zhenling Deng; Xinliang Lu; Xiaohua Wang; Weihua Zhang; Hua Jin; Jun Su; Tao Jiang; Huan Ren (Molecular and Cellular Biochemistry, 2012)